THE MAIN ELEMENTS OF ACCOUNTING POLICIES AND METHODS IN FRUIT AND VEGETABLE PROCESSING ENTERPRISES (Global Conference on Multidisciplinary Research and Innovation, 2026)
This study examines the main elements of accounting policies and methods in fruit and vegetable processing enterprises. These enterprises transform perishable raw materials into high-value finished products, creating added value for domestic and export markets. The research highlights how accounting policies integrate stages such as raw material receipt, preparation, technological processing, packaging, storage, and sales into a unified system, ensuring accurate cost calculation, reliable financial reporting, and effective management decision-making. Special attention is given to the industry’s biological and seasonal characteristics, including phenological waves, perishability, and cold chain requirements. Key elements analyzed include recognition and measurement methods, cost calculation and allocation, accounting for losses and by-products, quality-based price adjustments, and internal control and audit mechanisms. The study demonstrates that sound accounting policies are critical for production stability, financial forecasting, and compliance with domestic and international market standards.
Keywords: Fruit and vegetable processing, accounting policies, cost calculation, recognition and measurement methods, internal control, by-products, quality-based price adjustments, financial reporting, cold chain.